PERANCANGAN PARAMETER PRODUK BATA INTERLOCK PT SEMEN PADANG BERDASARKAN STANDAR SNI 03-0349-1989 - Fauwaz El Muhammady, Faizun
PT Semen Padang is one of the first cement producers in Southeast Asia and has been operating for more than 110 years. Therefore, PT Semen Padang tries to make various innovations by developing interlock brick products by reason of the housing developer's need for fast, easy, and quality development as well as customer needs for affordable homes. Interlock brick is also had various advantages over red bricks, especially in terms of cost savings and environmental friendliness. PT Semen Padang now is developing interlock brick products to conform to the standard. The development process of PT Semen Padang's interlock bricks has reached the stage of making a prototype model house. The existing interlock brick products of PT Semen Padang have not been adjusted to the physical parameters of SNI 03-0349-1988 based on discussions with the production party of PT Semen Padang interlock bricks. Therefore, this research was conducted to find the best product parameter of PT Semen Padang interlock brick products based on the physical parameters of SNI 03-0349-1989. The search for the best composition of interlock bricks was carried out using the Taguchi experiment. Taguchi's experimental method consisted of three groups of stages. The first group of stages is pre-experiment, which aims at experimental factors and responses and making experimental combinations with orthogonal matrixes. The second stage group is an experiment in the form of a process of calculating the experimental response. The third stage group is post-experimental in the form of data processing by finding the optimal value of each factor in each experimental response. Based on the study's results, it was found that the optimum level combination for compressive strength parameters based on SNI 03-0349-1989 is a material ratio of 1:4, the percentage of water is 3%, and the type of material is cement (1) + mixed sand (4). The optimum level combination for water absorption parameters based on SNI 03-0349-1989 is a material ratio of 1:4, the percentage of water is 1%, and the type of material is cement (1) + mixed sand (4).